2020
DOI: 10.1186/s12906-020-03167-0
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Uyghur medicine Quercus infectoria galls water extract triggers apoptosis and autophagic cell death in colorectal cancer cells

Abstract: Background The water extract of Quercuse infectoria galls (QIG) is the active ingredient of Uyghur medicine Xipayi Kui Jie’an (KJA) which has promising therapeutic effects on Ulcerative Colitis (UC) as an alternative medicine. Considering the relationship between UC and the development of colorectal cancer (CRC), the present work aims to explore the direct anti-CRC activity of QIG extract. Methods CCK8 assay and flow cytometry were used to detect cytotoxicity and apoptosis. Transmission electron microscopy (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Autophagy may protect cells from death or accelerate cell death in diferent physiological conditions [37]. Some studies consider that excessive autophagy is a major cause of cell death [38], whereas some studies argue that excessive autophagy reduces apoptosis and promotes cell survival [39]. Analysis of related proteins showed that cleaved caspase-3 and cleaved-PARP were downregulated after treating HCQ, while they were upregulated in the rapamycin group.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy may protect cells from death or accelerate cell death in diferent physiological conditions [37]. Some studies consider that excessive autophagy is a major cause of cell death [38], whereas some studies argue that excessive autophagy reduces apoptosis and promotes cell survival [39]. Analysis of related proteins showed that cleaved caspase-3 and cleaved-PARP were downregulated after treating HCQ, while they were upregulated in the rapamycin group.…”
Section: Discussionmentioning
confidence: 99%
“…Research reports show that QIG is rich in tannins with about 50–70%, followed by gallic acid, ellagic acid, hexamethyl, syringic acid, amentoflavone, sitosterol, and glucose propionic acid. It has various pharmacological activities, including antifungal, antiviral, insecticidal, wound healing, gastric protective effects, and anti-inflammation ( Zhang et al, 2020 )…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the gall extract significantly suppressed the epithelial mesenchymal transition (EMT) process known to be involved in tumorigenesis and migration of cancer cells. In addition, the activated extracellular signal-regulated kinase (Erk) signaling pathway promoted the autophagic CRC cell death [45].…”
Section: Anticancer Activitymentioning
confidence: 99%